Effect of perforations on axially loaded I-section cold-formed steel column - Nur Zayani, Zaharudin (2017)
Cold-formed steel structure are steel structural product that are made by bending flat sheets of steel at ambient temperature into shapes. The application of cold-formed steel is an extent to the Industrialized Building System (IBS) that promotes high quality of work with minimum waste. Cold-formed steel comes with various type of section based on their function and purpose in construction work. There are three main type of sections which are single open section, open built-up section and closed built-up section. This research will be concentrating on open built-up section or I-section. Structural members of cold-formed steel usually come with the presence of perforations. Perforations is a hole or opening that are made on the cold-formed steel to ease construction work. It usually provided with different shapes and size based on its function such as to accommodate electrical, plumbing and air conditioner or heating services. However, the presence of perforations may cause a reduction in strength of individual component elements and the overall strength of the member depending on the position, size and orientation of the opening. This research will focus on the effect of position and shape of the perforations on the structural strength of the axially loaded cold-formed steel column. An experimental investigation of cold-formed steel subjected to compression loading to study the effect of perforations on the load capacity of column members of built-up I-section is held. A total of 6 samples that have different position of perforations were tested in this experiment. Each member has nominal thickness of 1.6 mm, column length of 600 mm and were compressed between a simply supported end at both end. The result of this experiment shows that the ultimate load of each sample varies greatly on the perforation position. The result is presented in three section which are load vs vertical displacement, load vs horizontal displacement and buckling behavior.